Extraction of Vanadium and Chromium from the Material Containing Chromium, Titanium and Vanadium - Sheng Huang; Shengfan Zhou; Fuhong Xie; Bianfang Chen; Biao Liu; Qi Ge; Mingyu Wang; XUEWEN WANG (The Minerals, Metals and Materials Society, 2018)
To recover iron, titanium, vanadium and chromium from vanadium bearing titanomagnetite, a process of direct reduction has been proposed. After magnetic separation, a material containing titanium, vanadium and chromium was obtained. In this paper, a salt-roasting process was proposed to extract vanadium and chromium from the material containing titanium, vanadium and chromium. The effects of the several parameters that included roasting temperature, roasting time and the addition of sodium carbonate were investigated. Under the most suitable conditions including a roasting temperature of 900 °C, roasting time of 2 h and sodium carbonate addition of 33 wt%, the leaching of vanadium and chromium reached 91.2 and 68.4%, respectively. After leaching, the leach residue can be used as the raw material for extraction of titanium.